A Cavity in the Infectious Differential: An Atypical Pulmonary Lesion - Dr Bradford Becken; Dr Andrea Green Hines; Dr Abigail Drucker (International Journal of Infectious Diseases)
Background: Pulmonary endometriosis is a rare form of endometriosis, with the diagnosis often missed or delayed as infectious etiologies are often higher on the differential. Case Description: A 13-year-old female, presented to the local children's hospital with 18 months of periodic hemoptysis, shortness of breath with exertion, and a 4kg weight loss. Her medical history was non-contributory aside from a spontaneous left apical pneumothorax that coincided with the start of the hemoptysis. A chest X-ray showed a right upper lobe cavitary lesion. Infectious Diseases was then consulted to assist with management. A chest CT scan confirmed the cavitary lesion, and the patient underwent bronchoscopy, and testing for tuberculosis and histoplasmosis. The bronchoscopy showed erythematous mucosa. An interferon gamma release assay was negative, as were acid-fast stains from her bronchoscopy and sputum samples.At follow-up, symptoms were unchanged. Testing for echinococcosis, paragonimiasis, HIV, hepatitis B & C, sarcoidosis and ANCA-mediated vasculitis was negative. The patient was then evaluated by gynecology, and reported monthly cycles lasting 5 days without dysmenorrhea. A review of the timing of the episodes of hemoptysis was suggestive of pulmonary endometriosis. The patient was counseled on hormonal medications with the goal of inducing atrophy of the pulmonary endometriosis lesion, but she declined for fear of medication induced weight gain. Discussion: Endometriosis affects up to 15% of postmenarchael females, causing pain and cramping during menstruation. While endometriosis is often confined to the pelvis and abdominal cavity up to 12% involve thoracic spread. The pathogenesis of pulmonary endometriosis is unclear, but theories include hematologic spread of stem cells and coelomic metaplasia in which epithelial cells may be stimulated to differentiate into endometrial cells. Patients with pulmonary endometriosis often present with symptoms years after the onset of pelvic endometriosis. Cases of isolated thoracic endometriosis are rarer, and the majority have pleural over parenchymal involvement.Because of the atypical symptoms of pulmonary endometriosis, a diagnosis if often delayed or missed. In patients with cavitary lesions and hemoptysis, tuberculosis and histoplasmosis are often the primary suspected etiologies. Catamenial pneumothorax is often the presenting symptom, with the initial diagnosis missed in this case. Diagnosis is often made with a combination of patient history, imaging and bronchoscopy, but bronchoscopy results are affected by the timing of the study with the patient's menses. Treatment of pulmonary endometriosis mirrors that of pelvic endometriosis; pharmacologic contraceptives and surgery, though definitive guidelines do not exist. Common complications of pulmonary endometriosis include ongoing bleeding, chronic cough, pulmonary scarring and catamenial pneumothorax, resulting in the need for recurrent medical and procedural interventions. Conclusion: While pulmonary cavitary lesions are suggestive of tuberculosis, in postmenarcheal females, pulmonary/thoracic endometriosis should be considered, especially if accompanied by ground glass opacities on imaging and unexplained pneumothorax.